Optimasi dan Otomasi Pengaturan Kerja pada Sekolah - Lestari, Astri Puji; Iberahim, Habibi; Devi, Kiki Amelia; Yaqin, Muhammad Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Schools are formal educational institutions that are very important for the nation's children. Schools can successfully carry out the education process well, certainly not apart from the factors that support the success of the education process. In schools there are also several activities that will be carried out. It is necessary to arrange school working hours to carry out all these activities. This is in accordance with Ministerial Regulation No. 23 of 2017 concerning School Days, which regulates schools 8 hours a day for 5 days a week, and is officially implemented in the 2017-2018 school year. In addition to teaching, educators also become a committee in carrying out other activities at the School. It is necessary to assess criteria for each position including the amount of workload so that the burden of each person can be evenly and optimally. This problem can be solved by building a Decision Support System (SPK) application using the Profile Matching method. In this study, Profile Matching is used to recommend the best name for a position in the committee based on rank. Assessment is based on aspects of each position, which consists of core factors and secondary factors. Using this method can produce an optimal committee composition according to available resources and schedules.